Thermally-activated constitutive model including dislocation interactions, aging and recovery for strain path dependence of solid solution strengthened alloys: Application to AA5754-O. (December 2015) - Pham, Minh-Son; Iadicola, Mark; Creuziger, Adam; Hu, Lin; Rollett, Anthony D.
Abstract: A thermally-activated constitutive model is developed based on dislocation interactions, crystallographic orientations and microstructural evolution to describe the elasto-plastic stress–strain behavior during multi-axial loading. The aim is to contribute to the quantification of complex strain path response in solid solution strengthened alloys. In detail, dislocation/dislocation interactions are incorporated in the model to quantify latent and kinematic hardening phenomena during loading path changes. Dislocation density-based constitutive relations are included to account for dislocation features such as dislocation forests, walls and channels. Moreover, dislocation/solute atom interactions are also considered in order to account for both dynamic and static strain aging as well as static recovery. The model is validated against multiple multi-axial data sets for AA5754-O with changes of loading path and various degrees of pre-strain and time intervals between tests. Highlights: A thermally-activated constitutive model is developed. Latent and kinematic hardening are included by dislocation interactions and texture. Dynamic recovery is modelled by dislocation densities and evolving similitude factor. Dislocation–solute interaction is considered for strain aging and static recovery. Flow stress behavior of AA5754 during complex loading paths is accurately modeled.